AGROBISNIS SEKTOR PETERNAKAN AYAM BROILER - -, Astuti (Universitas Negeri Yogyakarta, 2003)
Problemsof educated (university graduates)unemployedpeopleshould besolved1;-:eirel-wastemanpowers.Aneffort toreformthegraduates,therefore theycanhelpr:=selvesby creatingtheir own jobs was conducted. The universitygavesome expertise–;:::-rentrepreneurattitudes and skills through aprogramcalles